(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the diagnostic accuracy of mammography in characterization of palpable breast lumps in benign and malignant; keeping histopathology as a gold standard. Study Design: Observational / analytic study. Place and Duration of Study: The study was conducted in Department of Radiology, Ittefaq Hospital (Trust) Lahore in six months duration from July 2013 to January 2014. Patients and Methods: 300 female patients with palpable breast masses were included in the study. All patients had mammography done to establish diagnosis as benign or malignant, followed by histopathology of the mass (as gold standard) to detect the lesion as benign or malignant. Diagnostic accuracy of mammography was detected by determining sensitivity, specificity and accuracy. Results: Sensitivity, specificity, and accuracy of mammography were 95.3%, 95.4% and 95.3%, respectively. Conclusion: The sensitivity, specificity and accuracy of mammography is high for characterization of palpable breast masses as benign or malignant.